Regional Innovation System And Local Economic Development In Indonesia - Adiwan F Aritenang (TATALOKA, 2013)
In Indonesia, decentralization and globalization has introduced a new spirit for localism. Since decentralisation, regions have been motivated to accelerate economic development through local endowment and resources. The democratic Indonesia government has been interested to follow economy theories and case studies develop in the advance countries. Over the years, government policies have supported and strengthen technology development through industrial clusters and national and regional innovation systems. This research aims to explore current progress of Indonesia innovation system through industrial clusters. The research found the presence of industry clustering and very limited innovation system in Indonesia. The research argues that these activities has significant impact on employment growth, but does not increase the industry's value added.